Sustainable tourism competitiveness: reflections from theory and practice - Villa-Zamorano, Zyanya María (RITUR - Revista Iberoamericana de Turismo, 2025)
Tourism competitiveness is a crucial factor for the sustainable development of destinations in a globalized environment. This article examines trends in its approach from both theoretical and practical perspectives, integrating a review of recent literature with findings from an interdisciplinary panel conducted during the XVI International Patrimonial Chair in Tourism "Sergio Molina". The panel brought together key stakeholders from academic, governmental, and business sectors, who offered insights into strategies and challenges related to tourism competitiveness. Using a qualitative approach based on grounded theory, key categories were identified, including sustainability, technological innovation, cooperation and governance, education and cultural preservation, and the quality of the visitor experience. The results underscore that sustainability serves as a central axis connecting multiple dimensions, fostering responsible practices that encompass both environmental conservation and the social and economic inclusion of local communities. Technological innovation emerges as a strategic tool for modernization and global visibility, although it must be balanced with the authenticity and quality of tourism experiences. Similarly, collaborative cooperation and governance are highlighted as essential pillars for coordinating intersectoral efforts and addressing challenges such as overtourism. Finally, the quality of the visitor experience and education play pivotal roles in cultural preservation and in strengthening the identity of destinations. This article concludes that an integrated approach—grounded in sustainability, balanced innovation, and ethics—is vital to enhancing tourism competitiveness. Moreover, it outlines directions for future research to deepen the understanding of these factors and their practical application in designing strategies for more competitive and responsible tourism.